2015
DOI: 10.3727/096368915x687011
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Dentate Progenitor Cells Show Increased Survival in an Enriched Environment but Do Not Exert a Neurotrophic Effect on Spatial Memory within 2 Weeks of Engraftment

Abstract: Cyclin D2 knockout mice show decreased levels of endogenous dentate neurogenesis. We investigated whether transplanted dentate progenitor cells from wild-type mice respond in vivo to an enriched environment and whether they improve deficient dentate neurogenesis through a neurotrophic effect. Adult cyclin D2 knockout mice were transplanted with passaged adult progenitor cells and kept in an enriched environment or under standard housing conditions in isolation. After 1 week, animals living in an enriched envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Transplantation studies are one possibility to enlighten the interplay between cell-intrinsic and cell-extrinsic factors in the regulation of aNSC properties and have been carried out in a variety of transplantation sites with various graft origins: the homotopic transplantation of PVR V-SVZ aNSCs provided large numbers of neurons with a typical olfactory bulb interneuron morphology [ 44 ], but other studies using heterotopic grafting of either PVR V-SVZ aNSCs or neuroblasts yielded contradictory results, with either a predominant astroglial or neuronal differentiation independent of host specifications such as increased age or dopaminergic differentiation [ 45 , 46 , 47 , 48 , 49 ]. Similarly, hippocampal aNSCs display a robust neuronal differentiation after homo- and heterotopic grafting into neurogenic regions, but a strict astroglial differentiation otherwise [ 50 , 51 , 52 , 53 ]. A recent study even reported the acquisition of neuronal properties of grafted aNSCs through a fusion with resident neurons of the host brain [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation studies are one possibility to enlighten the interplay between cell-intrinsic and cell-extrinsic factors in the regulation of aNSC properties and have been carried out in a variety of transplantation sites with various graft origins: the homotopic transplantation of PVR V-SVZ aNSCs provided large numbers of neurons with a typical olfactory bulb interneuron morphology [ 44 ], but other studies using heterotopic grafting of either PVR V-SVZ aNSCs or neuroblasts yielded contradictory results, with either a predominant astroglial or neuronal differentiation independent of host specifications such as increased age or dopaminergic differentiation [ 45 , 46 , 47 , 48 , 49 ]. Similarly, hippocampal aNSCs display a robust neuronal differentiation after homo- and heterotopic grafting into neurogenic regions, but a strict astroglial differentiation otherwise [ 50 , 51 , 52 , 53 ]. A recent study even reported the acquisition of neuronal properties of grafted aNSCs through a fusion with resident neurons of the host brain [ 54 ].…”
Section: Introductionmentioning
confidence: 99%